(untitled) (مجلة إحالات, 2026)
Translation is converting a written text from the source language into another one in the target language, whether we deal with scientific or literary texts. If we want to talk about literary translation, especially poetry, on one hand, we can perceive that the last is the most difficult type of translation at all. On the other hand, some others said that it is impossible to effect such task successfully. From what it is mentioned above, : This research is focused on translating english poetry into arabic where such process is based on two main factors: speciality and fidelity. The study is aming to determine how can the former factors impact on selecting methods and techniques adopted by both translators to produce an equivalent poetry to the original one as much as possible.